CORONAVIRUS DISEASE 2019 (COVID-19) ASPECTS OF INTEREST FOR CRITICAL CARE. .: NARRATIVE REVIEW - Diaz Ballve, Ladislao (Revista Argentina de Terapia Intensiva, 2020)
Coronaviruses are so named because of the shape of the corona on their surface. They are RNA viruses that belong to the Coronvirinae subfamily, of the Coronaviridae family of the order Nidovirales. They have four main subgroups: alpha, beta, gamma, and delta, depending on their genomic structure. Alpha and beta coronaviruses infect mammals only, generally causing respiratory symptoms in humans and gastroenteritis in other animals. As of December 2019, only six different coronaviruses were known to infect humans. Four of these (HCoV-NL63, HCoV-229E, HCoV-OC43, and HKU1) caused mild, cold-like symptoms common in immunocompetent individuals, the other two have caused pandemics in the past two decades. In 2002–2003, the severe acute respiratory syndrome coronavirus (SARS-CoV) caused the SARS epidemic that resulted in a 10% mortality. And the Middle East Respiratory Syndrome (MERS-CoV) coronavirus caused a devastating pandemic in 2012 with a 37% death rate. At the end of 2019, in a group of cases of patients with viral pneumonias, in the city of Wuhan, Hubei province, China, a new beta coronavirus was identified, first called the novel coronavirus 2019 (2019-nCov).